A snapshot of Introductory Pharmacy Practice Experience program characteristics - Yu, Frank; Cox, Brittney; Jehle, Gretchen; Richter, Lisa; Sewell, Jeanna; Smith, Mary Douglass; Tran, Emmeline (American journal of pharmaceutical education, 2024)
To provide S/COPs a snapshot of IPPE program characteristics to generate and share ideas for IPPE program modifications to improve student learning outcomes and comply with Standards 2025. A 41-item electronic survey was distributed to 140 ACPE fully accredited schools and colleges of pharmacy in 2023. IPPE program characteristics such as structure, learning activities, assessments, and requirements were described. Eighty-seven programs participated in the survey (62.1% response rate). Notable findings included 64.4% of programs starting IPPEs during the first professional year, 78.6% did not count simulation hours towards ACPE-hour requirements, 24.1% incorporated patient care electives, over 90% incorporated various patient care activities, 40.2% exceeded a 2:1 student to preceptor ratio, 15.7% incorporated layered learning, 50.0% incorporated interprofessional education, 57.5% used summative assessment rubrics based on Entrustable Professional Activities, and 77.0% used pass/fail grading. Due to evolving accreditation standards, the study provided valuable information about the current state of IPPEs. The study results included examples and components that programs can use to ensure that they comply with Standards 2025.